Thermal analysis and validation of UV and visible spectrophotometric methods for the determination of new antibiotic tigecycline in pharmaceutical product - Silva, Lucélia Magalhães da [UNESP]; Almeida, Adelia Emilia de [UNESP]; Salgado, Hérida Regina Nunes [UNESP] (Scientific & Academic Publishing, 2012)
This work has proposed the development and validation of ultraviolet (UV) and visible spectrophotometric methods for determination of tigecycline in lyophilized powder. In UV method tigecycline showed absorption maximum at 245 nm, in aqueous medium, where as in visible spectrophotometric method it reacts with copper acetate reagent, under acid conditions, forming a greenish coloured solution with absorption maximum at 378 nm. Thermogravimetric Analysis and Differencial Scanning Calorimetry (TGA-DSC) techniques were studied to determine the thermal analysis of tigecycline. The methods were completely validated according to the International Conference on Harmonization (ICH) guidelines, showing good accuracy, precision, selectivity, robustness and linearity. Therefore the methods were found to be simple, economic and free of polluting reagents, being suitable for the analysis of the lyophilized powder formulation, contributing to improve the quality control and to assure its therapeutic efficacy.
Keywords: Tigecycline; Spectrophotometric methods; Thermal analysis